ACADEMIC SUPERVISION BY THE SCHOOL PRINCIPAL IN IMPROVING JUNIOR HIGH SCHOOL TEACHERS' PERFORMANCE IN SUSOH DISTRICT, SOUTHWEST ACEH REGENCY - Mira Puspita; Nasir Usman; Qismullah Yusuf (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The performance of elementary school teachers in managing the learning process still requires attention from the school principal through academic supervision activities. Academic supervision is carried out in the process of coaching, mentoring, and development of teacher performance. If teachers adopt a static attitude (feeling sufficient with the knowledge/experience they already possess), then the educational process will also be static. Teacher performance cannot reach its maximum potential without guidance, encouragement, and motivation from certain parties, in this case, from supervisors. The aim of this research is to determine the academic supervision of the school principal in improving the performance of junior high school teachers in Susoh District, Southwest Aceh Regency. This research method uses a qualitative approach with a field study perspective. Data collection techniques include observation, interviews, and documentation. Data analysis techniques in this research use Miles and Huberman's data reduction, data presentation, and conclusion drawing stages. The results of the research show that 1) Implementation of Academic Supervision at Unggul Tunas Nusa State Junior High School, Susoh State Junior High School 2, and Susoh State Junior High School 1 has been carried out in accordance with existing provisions, including: a) classroom visits. b) classroom observation. c) visitation approach. d) teacher activity in carrying out teaching duties; 2) The results of the supervision conducted by the principal of Unggul Tunas Nusa State Junior High School are: teacher preparation in teaching (teaching materials), teacher activity in carrying out duties, and teacher attitudes and behavior are better compared to Susoh State Junior High School 2. The results obtained from the follow-up of classroom visit supervision at Susoh State Junior High School 1 are very satisfying because teachers who receive special notes in the teaching and learning process (PBM) become maximal in teaching and there are significant changes. Academic supervision conducted by the principal of Unggul Tunas Nusa State Junior High School through various stages such as coaching from the principal in providing input, ideas, or forms of reprimand is a good attitude for achieving educational progress. Based on the results of interviews and observations, providing guidance on learning evaluation as a form of follow-up. This guidance is directly from supervisors and principals conducted during the evaluation process. If the principal and the supervisory team find teachers having difficulties in conducting learning evaluations, the team will try to overcome them.